2020
DOI: 10.1111/pedi.13097
|View full text |Cite
|
Sign up to set email alerts
|

Markers of cholesterol synthesis are elevated in adolescents and young adults with type 2 diabetes

Abstract: Background: Changes in cholesterol absorption and cholesterol synthesis may promote dyslipidemia and cardiovascular disease in individuals with type 2 diabetes mellitus (T2DM). Objective: To assess cholesterol synthesis and absorption in lean individuals, obese individuals, and individuals with T2DM. Methods: We measured lathosterol and lanosterol (markers of cholesterol synthesis) as well as campesterol and β-sitosterol (markers of cholesterol absorption) in the serum of 15 to 26 years old individuals with T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Cholesterol excessive accumulation resulted in beta-amyloid and decreased cholesterol synthesis led to synaptic defects. Epidemiological data indicated a correlation between evaluated serum cholesterol and diabetes and prolonged sleep deprivation in humans which is contrary to the results in the brain [44,45]. This apparent contradiction can be elucidated by the presence of the blood-brain barrier (BBB), which establishes plasma cholesterol and intracerebral cholesterol as distinct systems.…”
Section: Discussionmentioning
confidence: 89%
“…Cholesterol excessive accumulation resulted in beta-amyloid and decreased cholesterol synthesis led to synaptic defects. Epidemiological data indicated a correlation between evaluated serum cholesterol and diabetes and prolonged sleep deprivation in humans which is contrary to the results in the brain [44,45]. This apparent contradiction can be elucidated by the presence of the blood-brain barrier (BBB), which establishes plasma cholesterol and intracerebral cholesterol as distinct systems.…”
Section: Discussionmentioning
confidence: 89%
“…Body mass index and abdominal obesity were associated with at least one abnormal lipid level [29]. Cholesterol synthesis markers are higher in adolescents and young adults with type 2 diabetes than in lean subjects and are positively correlated with BMI, TG, hyperinsulinemia, hyperglycemia, and inflammation [30].…”
Section: Discussionmentioning
confidence: 98%
“…Some people had high absorption and some people had high synthesis. Other studies have shown that patients with type 2 diabetes and metabolic syndrome have high cholesterol synthesis [ 17 19 ], while patients with type 1 diabetes and familial hypercholesterolemia have high cholesterol absorption [ 20 22 ], further explaining the characteristics of individual differences in cholesterol absorption and synthesis.…”
Section: Discussionmentioning
confidence: 99%